2020
DOI: 10.1038/s41598-020-64016-1
|View full text |Cite
|
Sign up to set email alerts
|

Markers of tissue damage and inflammation after robotic and abdominal hysterectomy in early endometrial cancer: a randomised controlled trial

Abstract: The aim of this study was to analyse the dynamics of tissue damage and inflammatory response markers perioperatively and whether these differ between women operated with robotic and abdominal hysterectomy in treating early-stage endometrial cancer. At a Swedish university hospital fifty women with early-stage low-risk endometrial cancer were allocated to robotic or abdominal hysterectomy in a randomiszed controlled trial. Blood samples reflecting inflammatory responses (high sensitivity CRP, white blood cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Within this grade, we were able to demonstrate that robot-assisted colorectal surgery elicited less marked cortisol elevation than a more invasive open procedure. Similar observations have been made for laparoscopic and open cholecystectomy [ 48 ], robotic radical prostatectomy and open retropubic approach [ 49 ], and for robotic and open hysterectomy [ 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…Within this grade, we were able to demonstrate that robot-assisted colorectal surgery elicited less marked cortisol elevation than a more invasive open procedure. Similar observations have been made for laparoscopic and open cholecystectomy [ 48 ], robotic radical prostatectomy and open retropubic approach [ 49 ], and for robotic and open hysterectomy [ 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…In patients undergoing hysterectomy, CRP levels were lower after laparoscopic hysterectomy than abdominal surgery. 1,6,11,18 To the contrary, other researchers found no post-operative difference in CRP between abdominal and laparoscopic hysterectomy, and the authors asserted that this was related to the longer operation time or extensive electrocoagulation in the laparoscopy group. 11 In agreement with previous studies, the post-operative increase in levels of CRP was significantly higher in the laparotomy group than in the laparoscopy group.…”
Section: Discussionmentioning
confidence: 98%
“…6 Increasing interest in laparoscopic hysterectomy has occurred since it was first reported in 1989. 1 Several studies comparing abdominal and laparoscopic hysterectomy, found the later to more beneficial in terms of lower complication rate, less postoperative pain, less blood loss, shorter hospital stay, shorter healing time and earlier return to daily activities. 2,6 Still, studies report that laparoscopic hysterectomy takes longer operative time than abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although without extra oral digitalis and diuretic drugs for 3 months like the surgical group, the MIPDO group showed comparable perioperative cardiac performance including the postoperative diminution of left atrial diameter, left ventricular end-diastolic dimension and right ventricular diameter, these immediate outcomes of MIPDO were consistent with the expected hemodynamic change: once the VSD was closed, the overloaded right ventricle and left atrium would tent to become normalized and initiate structural remodeling. Furthermore, patients in the MIPDO group showed minor elevation of WBC, CK, LDH and BUN, outgrowth of slighter inflammatory response (27) and milder renal function impairment (28,29). Although patients in MIPDO group were prescribed with heparin and oral aspirin, they presented similar or even less variation in PLT compared with surgical groups.…”
Section: Discussionmentioning
confidence: 99%